ASPIRASI KARIR, REGULASI DIRI, DAN SELF-PERCEIVED EMPLOYABILITY PADA MAHASISWA - Sawitri, Dian Ratna; Dewi, Kartika Sari (Faculty of Psychology, Diponegoro University, 2018)
Self-perceived employability is individual’s perceived ability to get sustainable employment appropriate to one’s qualification level. Previous researches demonstrated the importance of self-regulation in shaping self-perceived employability in emerging adulthood, when career aspirations have a significant role in career-related decision-making process. However, the relationships between career aspirations, self-regulation, and self-perceived employability among university students were rarely known. This study examined a theoretical model, whether self-regulation served as a partial mediator between career aspirations and self-perceived employability. Using a convenience sampling, we involved 600 university students who were at their second, fourth, sixth, eighth, and tenth semester (68% female, M age = 19.97 years; SD = 5.57) from a university in Semarang. Structural equation modeling demonstrated that career aspirations were associated with self-perceived employability directly and indirectly via self-regulation. It means, the higher students career aspirations, the better their self-regulation and self-perceived employability. Self-regulation also leads to higher self-perceived employability. We interpreted the findings of this study form developmental and goal-setting perspective. To promote self-perceived employability, students are recommended to boost their career aspirations and develop a good self-regulation skill.